Survey of Lichen at Swamp Forest in Plant Genetic Protection Area, Rambhai Barni Rajabhat University - สมนึก ชวัลรัตน์; การบุญ พิสุทธิ์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
Lichen at swamp forest in Plant Genetic Conservation Project under the Royal Initiative of Her Royal Highness Maha Chakri Sirindhorn, Rambhai Barni Rajabhat University were surveyed in January - October 2018. The lichens were collected on both sides of the nature trail of swamp forest (about 220 meters), together with environmental data collection. Total of 53 samples were examined the morphology, taxonomy and chemical composition by spot test in laboratory. The predominance of taxa belonging to the crustose lichen (96.23 %) and only 2 samples were foliose lichen (3.77 %). The lichen samples were identified into 10 family, 16 genus and 27 species. The third largest family of lichen were Graphidaceae (7 genus, 11 species and non-identify 1 species, 26 samples), followed by Pyrenulaceae (1 genus, 3 species and non-identify 1 species, 8 samples) and Malmideaceae (1 genus, 1 species and non-identify 1 species, 6 samples), representing 49.06, 15.09 and 11.32, respectively. In which, these three lichens are usually grow in humid and shady environments.